Self-Administered Heroin and Cocaine Combinations in the Rat: Additive Reinforcing Effects—Supra-Additive Effects on Nucleus Accumbens Extracellular Dopamine - Smith, James E (2006)
The concurrent use of cocaine and opiate combinations (speedball) has increased since the 1970s and now represents a growing subset of intravenous drug abusers. An isobolographic analysis was applied to the ascending limb of the dose–effect curves for rat self-administration of cocaine, heroin, and their combination to determine the nature of the interaction. The addition of heroin to cocaine shifted the dose–effect curve for self-administration to the left, and the modulation in reinforcing efficacy of the combination of cocaine and heroin was found to be additive. A second experiment used microdialysis to determine the effects of this drug combination on nucleus accumbens (NAc) extracellular levels of dopamine ([DA](e)) in rats self-administering low doses of cocaine, heroin, or cocaine/ heroin combinations. These doses of cocaine and cocaine/heroin combinations significantly increased NAc [DA](e), while heroin alone did not. The ratio of the % baseline of [DA](e) (or the dialysate concentrations of DA) to cocaine in the dialysate was higher during self-administration of cocaine/heroin combinations than with cocaine alone. These data indicate that although the interaction between cocaine and heroin in maintaining self-administration is additive, a potentiation of NAc dopaminergic neurotransmission is present, suggesting that NAc [DA](e) may not be a direct measure of reinforcing efficacy and/or it is not central to the mediation of the self-administration of this drug combination.